Operation reliability index for maintenance decision making in bridges - Lajevardi, Sadegh (2020)
Maintenance management developed by several approach to optimize cost recently. Meanwhile decision making during operation is difficult task for mangers to keep them safe as well as stakeholder demands satisfaction and costs with regard to resources limitation. This paper presents an approach for decision making process to select alternatives based on their costs. For this manner, the uncertainty of defect probability combine with other availability and performance features to find priority of maintenance equipment and their reliability. This multi-dimensional decision making do not deal with the essential imprecision of subjective judgment based on quantitative evaluation. To demonstrate the use and capability of the model, a case study is presented. In this case, results shows the quality value combined by delay as an effectiveness parameters (91.08) and then decision tree will complete it by risk and reliability factors.